The use of Kashubian regional architecture in the creation of a cultural heritage tourism offer in the rural areas of selected communes of the Pomeranian Voivodeship (Geography and Tourism, 2022)
In Kashubia, as a cultural region, tourism manifests itself in various forms. One of them is rural cultural tourism,utilizing, inter alia, the material assets, unique character and wealth of secular and sacred architecture. The aim ofthis article is to determine the use of Kashubian regional architecture in the creation of a cultural heritage tourism offer in selected communes of the Pomeranian Voivodeship. Research conducted by the author has shown that Pomeranian historic objects of sacred and secular architecture can be used to develop the heritage tourism offer, consistent with the idea of sustainable tourism. Some of the facilities are part of existing tourism products, e.g. cultural routes, museums, and theme parks, such as the Kashubian Ethnographic Park in Wdzydze Kiszewskie. However, the tourist potential of numerous  monuments is not fully used mainly due to insufficient tourism development, as well as lack of reliable information and promotion, and this affects sightseeing.